2013
DOI: 10.1210/jc.2012-3179
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Growth Arrest-Specific 6 Protein Is Associated With Adiposity, Systemic Inflammation, and Insulin Resistance Among Overweight and Obese Adolescents

Abstract: Circulating Gas6 levels are strongly associated with adiposity, inflammation, and insulin resistance status among overweight and obese adolescents. The potential role of the Gas6/TAM system in the initiation of childhood obesity and obesity-associated complications deserves further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 43 publications
2
30
0
3
Order By: Relevance
“…4c). Other disease-related genes that were upregulated by CR were the diabetes-related ankyrin repeat protein ( ANKRD23 ), whose expression in SM is increased under diabetic conditions [51] and the growth arrest-specific 6 ( GAS6 ) gene, which is strongly associated with adiposity, inflammation, and insulin resistance status among overweight people [52] (Fig. 4c).…”
Section: Resultsmentioning
confidence: 99%
“…4c). Other disease-related genes that were upregulated by CR were the diabetes-related ankyrin repeat protein ( ANKRD23 ), whose expression in SM is increased under diabetic conditions [51] and the growth arrest-specific 6 ( GAS6 ) gene, which is strongly associated with adiposity, inflammation, and insulin resistance status among overweight people [52] (Fig. 4c).…”
Section: Resultsmentioning
confidence: 99%
“…We found that this cleavage, which generates a ‘soluble Axl’ (sAxl), also occurred when Axl was activated by cross-linking antibodies. Elevated sAxl in blood has recently been reported to mark multiple human disease and trauma states, including aortic aneurysm 37 , lupus flares 38 , pneumonia infection 39 , preeclampsia 40 , coronary bypass 41 , and insulin resistance 42 . We suggest that Axl cleavage, and the generation of a sAxl-GAS-6 complex, is triggered by the inflammation-induced exposure of PtdSer in these settings, and may be a broadly useful diagnostic biomarker for inflammation in human disease.…”
Section: Discussionmentioning
confidence: 99%
“…This dietary synergy was still evident in parameters such as female femur length and bone marrow adiposity measured in 30 week old mice using this high fat model (32). Vitamin K is fat soluble, hence, increasing levels of adiposity with increasing age may reduce serum levels of vitamin K, and therefore reduce levels of VKDPs produced by organs other than the liver (eg, bone specific osteocalcin) as the liver could be prioritised for the utilization of vitamin K for clotting fac- levels of Gas6 were associated with obesity (which displayed increased blood pressure (BP)) and insulin resistance in adolescents (34), and Gas6 levels were increased in the secretome from atherosclerotic plaques (35). These data suggest the increased levels of Gas6 in the aorta from female HF/HF offspring may, ultimately, result in greater susceptibility in these animals to vascular disease.…”
Section: Discussionmentioning
confidence: 99%